Influence of Religiosity on the Behavior of Buying Sports Apparel: A Study of the Muslim Market Segment in India - Baber, Hasnan (Organizations and Markets in Emerging Economies, 2019)
The paper is aimed to study the influence of religiosity on the behavior of buying sports apparel in the Muslim market segment of India. The data was collected from 1000 Muslim respondents from four states: Uttar Pradesh, Delhi, Uttarakhand, and Jammu & Kashmir. The paper has found that religion plays no role when Muslims buy sports apparel. They shop as any other religious person does. No other factor, even fashion and religious obligation, is influenced by religion, except for shopping enjoyment responsiveness, which is influenced by intrapersonal Islamic religiosity. The paper’s perspective in studying the religious influences will assist sporting apparel manufacturers to design new products that will meet the requirements of the large Muslim segment in India, which is neglected so far. It will help marketers to save their effort and energy which would be utilized for Muslim Population.